THE RELATIONSHIP OF THE INCIDENT OF METABOLIC SYNDROME AND OVERACTIVE BLADDER IN FEMALE PATIENTS AT DR. M. DJAMIL PADANG IN 2023 - Anggra Pramana; Bobby Indra Utama; Husna Yetti (Universitas Andalas, 2024)
Overactive Bladder (OAB) is a chronic medical condition that has a negative impact on an individual's health and quality of life. Cardiovascular problems are considered to be one of the risks associated with OAB where one of the higher cardiovascular parameters is metabolik syndrome. Aim to determine the relationship between metabolik syndrome and Overactive Bladder in female patients at Dr. M. Djamil Hospital Padang. Quantitative research with a case control design using a questionnaire according to the Overactive Bladder Symptom Score (OABSS) and examination based on metabolik syndrome symptoms. The research was conducted at Dr. M. Djamil Hospital Padang in November 2022 to September 2023. There were 60 respondents who were divided into the OAB (28/60) and no-OAB group (32/60). Most respondents were aged 50-59 years (45,0%), graduated from high school (53.3%), worked as housewives (76.7%) and had diabetes mellitus (78,3%). In this study it was also found that 48,3% of respondents suffered from hypertension and 45.0% suffered from obesity. A total of 46.7% of respondents experienced OAB symptoms with a higher percentage of OAB found in the metabolik syndrome group (76,7%) than no-metabolik syndrome group (16.7%). Bivariate analysis found a relationship between metabolik syndrome and overactive bladder symptoms (p = 0.000) with metabolik syndrome affected the incidence of overactive bladder by 16.4 times (OR 16.42, (CI 95% 4.56-59.07). There is a relationship between metabolik syndrome and the incidence of OAB.